Genome‐wide association discoveries of alcohol dependence. (November 2014) - Zuo, Lingjun; Lu, Lingeng; Tan, Yunlong; Pan, Xinghua; Cai, Yiqiang; Wang, Xiaoping; Hong, Jiang; Zhong, Chunlong; Wang, Fei; Zhang, Xiang‐Yang; Vanderlinden, Lauren A.; Tabakoff, Boris; et al.
<x xml:space="preserve">Abstract</x> Objective To report the genome‐wide significant and/or replicable risk variants for alcohol dependence and explore their potential biological functions. Methods We searched in PubMed for all genome‐wide association studies (GWASs) of alcohol dependence. The following three types of the results were extracted: genome‐wide significant associations in an individual sample, the combined samples, or the meta‐analysis (p < 5 × 10−8); top‐ranked associations in an individual sample (p < 10−5) that were nominally replicated in other samples (p < .05); and nominally replicable associations across at least three independent GWAS samples (p < .05). These results were meta‐analyzed. cis‐eQTLs in human, RNA expression in rat and mouse brains and bioinformatics properties of all of these risk variants were analyzed. Results The variants located within the alcohol dehydrogenase (ADH) cluster were significantly associated with alcohol dependence at the genome‐wide level (p < 5 × 10−8) in at least one sample. Some associations with the ADH cluster were replicable across six independent GWAS samples. The variants located within or near SERINC2, KIAA0040, MREG–PECR or PKNOX2 were significantly associated with alcohol dependence at the genome‐wide level (p < 5 × 10−8) in meta‐analysis or combined samples, and these associations were replicable across at least one sample. The associations with the variants within NRD1, GPD1L–CMTM8 or MAP3K9–PCNX were suggestive (5 × 10−8 < p < 10−5) in some samples, and nominally replicable in other samples. The associations with the variants at HTR7 and OPA3 were nominally replicable across at least three independent GWAS samples (10−5 < p < .05). Some risk variants at the ADH cluster, SERINC2, KIAA0040, NRD1, and HTR7 had potential biological functions. Conclusion The most robust risk locus was the ADH cluster. SERINC2, KIAA0040, NRD1, and HTR7 were also likely to play important roles in alcohol dependence. PKNOX2, MREG, PECR, GPD1L, CMTM8, MAP3K9, PCNX, and OPA3 might play less important roles in risk for alcohol dependence based on the function analysis. This conclusion will significantly contribute to the post‐GWAS follow‐up studies on alcohol dependence. (Am J Addict 2014;23:526–539)